Systemic Factors Related to Intraocular Levels of Interleukin-6 and Vascular Endothelial Growth Factor in Diabetic Retinopathy. (17th July 2019) - Jung, Byung Ju; Lee, Mee Yon; Jeon, Sohee
Abstract : This study is for identifying systemic factors correlating with intraocular levels of interleukin-6 (IL-6) and vascular endothelial growth factor (VEGF) in diabetic retinopathy. Forty-two consecutive patients undergoing pars plana vitrectomy (PPV) for PDR were included in this cross-sectional study. The aqueous humor was sampled just prior to PPV for assay of IL-6 and VEGF. One day before PPV, patient characteristics were recorded and a number of systemic markers were amassed, including fasting and postprandial glucose, homeostasis model assessment- (HOMA-) IR, HOMA-beta, C-peptide, insulin, total cholesterol, triglycerides, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, apolipoprotein- (Apo-) A, Apo-B, and lipoprotein A (Lp-A). Relationships between systemic determinants and intraocular cytokine levels were analyzed by regression analysis. Mean levels of IL-6 and VEGF were 15.3 pg/mL (range, 2.4–10124.5 pg/mL) and 21.1 pg/mL (range, 3.2–766.1 pg/mL), respectively. After adjustment for age, gender, duration of diabetes, and BMI, multivariate analysis showed significant association of smoking (p = 0.002 ) and HOMA-IR (p = 0.003 ) with intraocular IL-6 levels, while intraocular VEGF and systemic Lp-A levels correlated significantly (p = 0.032 ). Insulin resistance and smoking status impacted intraocular levels of IL-6, while intraocular VEGF levels were influenced by Lp-A. An appreciation for the relationship between systemic factors and intraocular cytokines may help elucidate the complex pathophysiology of diabetic retinopathy.